Does Urban Polycentric Structure Improve Carbon Emission Efficiency? A Spatial Panel Data Analysis of 279 Cities in China from 2012 to 2020 - Shihan Zhang; Yanxin Xue; Shuzhen Jin; Zhenghong Chen; Suiying Cheng; Wei Wang (ISPRS International Journal of Geo-Information)
Urban spatial structure, shaped by human intervention in the natural environment, impacts the functional space and socioeconomic efficiency of cities. Against this backdrop, this study investigates the linkage between urban spatial structure (USS) and carbon emission efficiency (CEE) in China from 2012 to 2020. This paper employs a nine-year dataset and spatial econometric models involving 279 prefectural cities in China. The study innovatively employs the Herfindahl index and the super-efficiency SBM model to evaluate the level of polycentric urban structure and CEE in these cities. It further explores the trends in spatial evolution and relevant characteristics of these factors. Additionally, the study applies the SDM to explore the spillover effect of urban polycentric structure on CEE. The study makes innovative use of the Herfindahl index and the super-efficiency SBM model to evaluate the level of polycentric urban structure and CEE in these cities, further exploring the trends in spatial evolution and relevant characteristics of these factors. Additionally, it applies the SDM to explore the spillover effect of urban polycentric structure on CEE. Robustness tests are carried out to confirm the findings. The results confirm that a polycentric structure significantly enhances carbon emission efficiency within a city. However, it adversely affects neighboring cities by reducing their carbon emission efficiency through negative spatial spillover effects. The results verify that a polycentric structure significantly enhances carbon emission efficiency within a city. However, it has an adverse impact on neighboring cities by reducing their carbon emission efficiency through negative spatial spillover effects.